The Chi. The complete second season [videorecording (DVD)] - Mitchell, Jason, 1987-; Latimore, Jacob, 1996-; Mwine, Ntare Guma Mbaho (20th Century Fox, 2019)
As Brandon works to make things right with Jerrika, Emmett tries to get custody of his son, with help from Jada. Meanwhile, Ronnie hopes to come to terms with his actions, and Kevin grapples with past traumas.